Flexible and Ecofriendly Keypad Based on Paper and Pencil - Er, Sahane Firdevs; Kalabey, Nurefsan; Hah, Dooyoung (IEEE-Inst Electrical Electronics Engineers Inc, 2023)
Pencil-on-paper electronics has gained growing interests as cost-effective, ecofriendly, flexible, and light-weight devices for various applications. In this letter, a flexible keypad employing pencil-on-paper capacitive touch sensors is presented. Spiral-type interdigitated sensors are interconnected via steel threads as well as graphite paths to constitute a ten-button keypad. Passivation of the sensors by means of acrylic paint coating works as protection against deterioration from bending, folding, and extended usage. Backing of the keypad with silicone provides extra durability. Sensor reading is administered by Arduino boards. The same manufacturing method is used to scale up the system to a 44-button keyboard. Functionalities of both systems are successfully demonstrated, and effectiveness of the passivation is verified.
Kalabey, Nurefsan/0009-0007-3867-7913; Hah, Dooyoung/0000-0002-1290-0597
Keywords: Tactile Sensors; Keyboards; Smart Homes; Sensor Systems; Sensors; Manufacturing; Steel; Capacitive Touch Sensor; Ecofriendly Manufacturing; Flexible Electronics; Paper-Based Electronics; Pencil Electrodes